2015
DOI: 10.1038/mto.2015.14
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric antigen receptor–engineered T cells as oncolytic virus carriers

Abstract: The use of engineered T cells in adoptive transfer therapies has shown significant promise in treating hematological cancers. However, successes treating solid tumors are much less prevalent. Oncolytic viruses (OVs) have the capacity to induce specific lysis of tumor cells and indirectly impact tumor growth via vascular shutdown. These viruses bear natural abilities to associate with lymphocytes upon systemic administration, but therapeutic doses must be very high in order to evade antibodies and other compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 49 publications
0
43
0
Order By: Relevance
“…Specifically, T cells loaded with VSV (77), reovirus (78), HSV (79), and Newcastle disease virus (80) have been delivered to tumors in mouse models. Previous studies have demonstrated that engineering T cells with chimeric antigen receptors (CARs) increases the delivery of VSV and VV to tumor cells and that CAR expression and function are not affected by the cell's infection with OV (81). Despite the efficient homing of T cells to tumors, carrier T cells have limited ability to amplify OVs (81), and moreover this clinical application is challenging and expensive.…”
Section: Enhancing the Efficacy Of Ovtsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, T cells loaded with VSV (77), reovirus (78), HSV (79), and Newcastle disease virus (80) have been delivered to tumors in mouse models. Previous studies have demonstrated that engineering T cells with chimeric antigen receptors (CARs) increases the delivery of VSV and VV to tumor cells and that CAR expression and function are not affected by the cell's infection with OV (81). Despite the efficient homing of T cells to tumors, carrier T cells have limited ability to amplify OVs (81), and moreover this clinical application is challenging and expensive.…”
Section: Enhancing the Efficacy Of Ovtsmentioning
confidence: 99%
“…Previous studies have demonstrated that engineering T cells with chimeric antigen receptors (CARs) increases the delivery of VSV and VV to tumor cells and that CAR expression and function are not affected by the cell's infection with OV (81). Despite the efficient homing of T cells to tumors, carrier T cells have limited ability to amplify OVs (81), and moreover this clinical application is challenging and expensive. A few studies have shown that the viability of carrier T cells can be significantly improved by attaching VSV to the membrane of T cells, allowing gradual release of oncolytic VSV into the tumor mass (82,83).…”
Section: Enhancing the Efficacy Of Ovtsmentioning
confidence: 99%
“…Finally, in a totally different and very preliminary approach, CAR-T cells have been used to deliver OV to the tumor ( 92 ). Circulating cells such as lymphocytes, monocytes, erythrocytes, or even platelets can bind viruses and have shown tumor-targeting properties ( 93 96 ).…”
Section: Oncolytic Viruses: the Ideal Allies For Car-t Cells?mentioning
confidence: 99%
“…Although they did not use CAR-T cells in their study, the concept of their study could be extrapolated for CAR-T cells as CIKs show inherent characteristics of tumor homing and cancer cell killing [86]. In line with this, a recent study by VanSeggelen et al shows that oncolytic viruses with either RNA or DNA genome can be loaded onto CAR-T cells and efficiently transferred to tumor cells [87]. The anti-tumor effect of these novel combinations of oncolytic virus and CAR-T cells is yet to be evaluated in case of colorectal cancer.…”
Section: Combination Of Oncolytic Viruses With T Cells Expressing mentioning
confidence: 99%